The sport marriage : women who make it work - Ortiz, Steven M., 1952- (Sport and society., 2020)
"Ortiz draws on studies he conducted over nearly three decades that focus on the marital realities confronted by women married to male professional athletes. These women, who are usually portrayed in unflattering and/or unrealistic terms, face enormous challenges in their attempts to establish and maintain functional marital and family lives while the husband routinely puts his career first. Ortiz defines the traditional sport marriage as a career-dominated marriage, illustrating how it encourages women to contribute to their own subordination through adherence to an unwritten rulebook and a repertoire of self-management strategies. He explains how they make invaluable contributions to their husbands' careers while adjusting to public life and trying to maintain family privacy, managing power and control issues, and coping with pervasive groupies, overinvolved mothers, a culture of infidelity, and husbands who prioritize team loyalty. He gives these historically silent women a voice, offering readers perceptive and sensitive insight into what it means to be a woman in the male-dominated world of professional sports"--